Propriedade intelectual, origem de capital e desenvolvimento tecnológico: A experiência brasileira - Graziela Ferrero Zucoloto (Instituto de Pesquisa Econômica Aplicada (IPEA), 2010)
– This paper analyzes the evolution of technological development in Brazil, considering the impacts of the Brazilian Intellectual Property Law, introduced in 1996, in Brazilian enterprises` patenting. Firstly, the paper presents the main debates about intellectual property rights. Then, it analyses statistics of patents fillings in Brazil. Finally, statistical models indentify the importance of the origin of capital in patentability in Brazil, and how the patentability was affected by legislation change in 1996.
Keywords: O34; F23; 330; Technischer Fortschritt; Immaterialgüterrechte; Patent; Brasilien